Combinatorial approach to prepare antioxidative protein hydrolysate from corn gluten meal with dairy whey: Preparation, kinetics, nutritional study and cost analysis. (January 2022) - Singh, Umesh; Kaur, Dalveer; Mishra, Vibhu; Krishania, Meena
Abstract: The current study represents a tailored combinatorial approach to prepare protein supplement from Corn Gluten Meal (CGM). The green solvent for deodorization followed by enzymatic hydrolysis for enriching in lysine was used to solve CGM problems, such as its off-odour and lack of lysine. Different protease enzyme sources, such as porcine pepsin and pancreatin (P1), plant protease, papaya papain (P2), and fungal source alkaline protease from Aspergillus oryzae (P3), were tested for CGM digestibility using liquid whey as medium (Dairy by-product) and its amino acid profile of hydrolysate. The alkaline protease from Aspergillus oryzae generated the highest degree of hydrolysis (DH) was 65.05% (w/w) with good lysine (3.89% w/v) and tryptophan (2.36% w/v) at optimal conditions. Besides, kinetics models were also analysed for P1, P2 and P3 hydrolysis of CGM with time. Further, CGM hydrolysate purified by tangential flow filtration (TFF) and the peptides of size up to 37 kDa were formed by alkaline proteolysis. The mixture of purified peptides possessed a high in-vitro antioxidant activity. The sale-up and cost analysis of the whole process was evaluated and revealed that the developed product is scaleable and can be marketable as protein supplements. Graphical abstract: Image 1 Highlights: Efficient utilization of corn gluten meal and dairy by-product (whey). Eliminated the off-odour of protein hydrolysate by using green solvent. Degree of hydrolysis (∼ 65%) by protease Aspergillus oryzae and its kinetics Increased lysine (3.97%) and tryptophan (1.36%) content in CGM hydrolysate. Estimated the production cost of protein hydrolysate at scale up level.